2021
DOI: 10.1080/0142159x.2021.1962832
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative healthcare education programmes for continuing professional education in low and middle-income countries: A Best Evidence Medical Education (BEME) systematic review. BEME Guide No. 65

Abstract: Background: Large discrepancies exist between standards of healthcare provision in high-income (HICs) and low and middle-income countries (LMICs). The root cause is often financial, resulting in poor infrastructure and under-resourced education and healthcare systems. Continuing professional education (CPE) programmes improve staff knowledge, skills, retention, and practice, but remain costly and rare in low-resource settings. One potential solution involves healthcare education collaborations between institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Developing a globally relevant curriculum on cancer is a significant challenge needing to address multiple considerations including local cancer prevalence, differences in language, technology and drug availability, cultural norms, and health care structure between HICs and LMICs. 160 Our results revealed that most curricula were designed and implemented within HICs, with only six programs developed in LMICs. 161 Therefore, existing curricula may not be suitable to implement globally and a new cocreated curriculum, one which reconciles the issues noted above and represents the global cancer burden, is needed.…”
Section: Discussionmentioning
confidence: 80%
“…Developing a globally relevant curriculum on cancer is a significant challenge needing to address multiple considerations including local cancer prevalence, differences in language, technology and drug availability, cultural norms, and health care structure between HICs and LMICs. 160 Our results revealed that most curricula were designed and implemented within HICs, with only six programs developed in LMICs. 161 Therefore, existing curricula may not be suitable to implement globally and a new cocreated curriculum, one which reconciles the issues noted above and represents the global cancer burden, is needed.…”
Section: Discussionmentioning
confidence: 80%
“…Hill et al described common barriers in their systematic review, including Western bias and cultural differences. Five progressive stages were identified that collaborators might need to navigate to have a successful and equal collaboration: personal values, relationships, resilience, benefits, and feed-forward [ 17 ]. We found that the systematic review by Hill et al provides an excellent framework for creating a collaborative program and can provide insight into current and past collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Any educative support an HIC NGO provides to an LMIC should, therefore, aim to provide the widest education to the greatest number of people, about conditions and their treatment that are relevant to their locality. That training should be able to deliver a sustainable service, affordable within the constraints of the human and technological assets available locally [24].…”
Section: Models For the Education Of Lmic Surgeonsmentioning
confidence: 99%